Continuity in transformation invariant social orderings two impossibilities - Fabella, Raul V. 1949- (The Philippine Review of Business and Economics, 1999)
We show that (1) a social ordering on R >= 0 that satisfies Strong Paretoness, Invariance with respect to a Positive Proportional Transformation and Lower Semi-Continuity does not exist and (2) that a social ordering on R > 0 that satisfies Weak Paretoness, Invariance with respect to an Affine Transformation and Lower Semi-Continuity is trivial.